Estudo da influência da condição de aderência entre camadas de pavimentos em seu comportamento mecânico - Scherer, Renan Gustavo (2018)
The performance of pavements is influenced by several factors. In the mechanisticempirical design, one of these is the bond condition at the interface of the constituent layers of the pavement. Despite this, this phenomenon is still a neglected topic in projects, and doubts persist even in the scientific environment about its occurrence and evaluation. The adherence is the ability of two different materials to remain united, suffering the same deformations when submitted to an external stress. According to their consideration, this parameter can generate different estimates of pavement performance and designs. The bond condition considered must be a reflection of the real behavior of the interfaces and, for this, it is necessary the correct evaluation of this. Several tests aiming at this determination have already been proposed, but are focused on the case of two agglutinated layers and difficult to apply to non-agglutinated layers. In this aspect, this research proposes the evaluation of the bond condition between a granular material layer and an asphalt concrete layer. A test was also designed to determine the adherence between the study layers based on interface shear. For this, a set of molds and a test equipment were developed that can be mounted on a Universal Testing Machine and allows the application of shear with normal stress action on the sample. This test allowed to obtain values of shear strength () and shear reaction modulus (K). The influence of the test temperature, the normal stress applied and the type of interface treatment used was evaluated. It was verified that the increase of the temperature leads to the reduction of and K, while the increase of the normal stress causes the increase of and K, as well as the application of prime coat in relation to the case without its use and, even more, the use of prime coat plus tack coat compared to the other two treatments. When comparing the results of K with values of literature used as limits of bonded or unbonded, it was found that these are together with the limit value indicating non-bonded. Due to, it was found that, for the evaluated cases, the interface is better characterized as unbonded. Also, were performed computational simulations, based on the average damage to fatigue, which indicated that the average damage values obtained with unbonded layers is greater than that obtained with bonded layers, indicating that the development and use of products and techniques that provide the adherence can lead to an improvement in pavement performance.